Modified Poly(p-phenylene benzoxazole) with Improved Thermal Property - Chen, Fenggui (Asian Journal of Chemistry, 2016)
Poly(p-phenylene benzoxazole) (PBO) with superior thermal property were widely used in many key areas. With the development of PBO application, higher thermal stability is required. In this contribution, modified PBO, containing different content of pyridine in the macromolecular chains, were prepared via direct polycondensation of salt monomer mixtures in poly(phosphoric acid). The salt monomer mixtures were synthesized by salification of 1,3-diamino-4,6-dihydroxybenzene dihydrochloride (DAR), terephthalic acid (TPA), 2,6-pyridinedicarboxylic acid (PDA) and 2,3,5,6-tetraaminopyridine (TAP). The obtained copolymers were characterized by Fourier transform infrared, elementary analysis, X-ray diffraction and thermogravimetric analysis. It can be found that PBO based copolymers modified with low dosage of PDA and TAP exhibit improved thermal property, whose thermal decomposition temperature with 10 % weight loss can reach 620 °C in air atmosphere.